Economic contribution of hunting expenditure to the southern United States of America. Issue 2 (3rd March 2016) - Poudel, Jagdish; Henderson, James E.; Munn, Ian A.
Abstract : Millions of people in United States of America (U.S.) participate in hunting activities which benefit the U.S. economy and help promote conservation and environmental goals. The 2011 National Survey of Fishing, Hunting and Wildlife-Associated RecreationSurvey reported that 13.7 million people aged 16 and above participated in recreational hunting activities, spending $33.7 billion on trips and equipment. This paper reports quantified economic contributions of hunting and its sub-activity expenditure for the thirteen states in the U.S. South by calculating total gross output, employment, total income, personal income and value-added. Input–output models were developed for each State, to determine the direct, indirect, and induced impacts of expenditure derived from hunting. Comparison at broad activity (hunting) and sub-activity (type of game etc.) levels revealed that there were differences in the individual states' economies, and that levels of expenditure affected the total economic contribution of hunting activities. Generally, states with larger economies benefited from greater multiplier effects while the total economic contribution, when expressed as a percentage of the economy, was greater for states with smaller economies.